Deep economic integration and state capacity a mechanism for avoiding the middle income trap?. - Laszlo,Bruszt (Metro Manila, Philippines Asian Development Bank, 2018)
This paper provides a conceptual framework, new measurement, and evidence. Focusing on a panel of European Union membership candidate countries, this paper documents the large variation in the evolution of state capacities and empirically identify key links and implementation sequences. The main result is the centrality of an intricate relationship between bureaucratic independence and judiciary capacity. Change in these two is a precondition for increasing internal and external competitions, which are key factors for successfully escaping the middle-income trap.
Keywords: Public sector and governance; Electronic books